Nice to watch? Students evaluate online lectures. (14th March 2017) - Sturman, Nancy; Mitchell, Benjamin; Mitchell, Amy
Summary: Background: Many clinical teachers who previously gave face‐to‐face lectures now record presentations for students to view asynchronously online. These teachers need to understand student expectations of online lectures (OLLs), and their place in the overall 'ecology' of student learning resources, in order to ensure that students watch, and learn from, their lectures. Methods: We conducted focus groups with a convenience sample of medical students undertaking their general practice placements, exploring student uses, evaluations and expectations of OLLs. Focus group discussions were recorded and transcribed verbatim. The transcripts were initially reviewed independently after each focus group by two of the authors, and then discussed. Descriptive categories and emergent themes were arrived at by an iterative consensus, and subjected to member checking. Teachers need to understand student expectations of online lectures and their place in the overall 'ecology' of student learning resources Results: Five focus groups were conducted with 36 students in total, and no new themes emerged after the third group. Students seem to attach importance to a number of factors within the categories of: (1) content, (2) organisation and structure, and (3) design and format. Discussion/conclusion: The OLLs delivered by clinical teachers seem to be valued by students, and to have a distinctive role within their overall learning resources. We suggest that the latter be curated coherently by faculty members, and that OLLs meet student expectations of relevance, brevity, focus, alignment with assessment, logical and transparent structure, sparing use of interactivity and distractions, and tight alignment of their content. Our findings may not be intuitive to clinical teachers more accustomed to face‐to‐face lectures, and may assist them to evaluate their OLLs.